Preparation of amine coated silver nanoparticles using triethylenetetramine - Ramajo, Leandro Alfredo (2009)
This article presents a simple method towards the preparation of functionalized silver nanoparticles in a continuous medium. Silver nanoparticles were obtained through AgNO3 chemical reduction in ethanol and triethylenetetramine was used to stabilize and functionalize the metal. The product was characterized with X-ray diffraction (XRD). Fourier-transformed infrared spectroscopy (FTIR), UV-visible spectroscopy, thermal gravimetric analysis (TGA) and transmission electron microscopy (TEM). Monocrystalline silver particles with cubic structure and an average size of 20 nm were obtained. The results reveal that it is possible to synthesize Ag nanopartieles functionalized with amine groups and that particle size is influenced by the processing route. © Indian Academy of Sciences.